Structural geology : the mechanics of deforming metamorphic rocks - Hobbs, Bruce E.; Ord, Alison, 1955- (Elsevier, 2015)
"The aim of this book is to discuss the processes that operate during the deformation and metamorphism of rocks in the crust and upper lithosphere of the Earth with the goal of understanding how these processes control or influence the structures that we observe in the field. The intent is to consider these processes within a framework set both by the individual mechanisms of deformation and the fundamental mechanics that describe and relate these mechanisms. Such mechanisms do not necessarily operate independently of each other but may be strongly coupled so that each process has strong feedback influences on the others leading to structures and mineral assemblages that do not develop in the uncoupled environment. The general system we consider in this book is a deforming, chemically reactive system in which fluid and thermal transport play significant roles"--